STRATIGRAFI BATUAN DAN KONDISI AKUIFER DI KAWASAN WISATA CANDI BOROBUDUR DAN PRAMBANAN - Ig. Setyawan Purnama (BPPT)
Borobudur and Prambanan Temples are icons of cultural tourism in Central Java and Yogyakarta. Increasing settlement, tourist and new facilities, especilly garden, cause the icreasing of groundwater usage. In the long term, the usage of groundwater that exceed the recharge can cause various impact such as land subsidence that can make damage of temples structure. The objectives of this study are to identify the rock stratigraphy in research area and know thecondition of aquifer and its groundwater potency. To achieve these goals, it is carried out geoelectric sounding in 10 samples point, namely five points in Borobudur Temple and five points in Prambanan Temple. To analyse sounding data, the resistivity data from field sounding are interpreted by Schlumberger O’Neil Programme. Base on the interpretation, can be determined rock stratigraphy, aquifer condition and qualitative potency estimation of groundwater in the research area. The results showed that the rock stratigraphy in sourrounding Borobudur and Prambanan Temples are different. The area surrounding Borobudur Temple consist of sand, gravel, tuff, lapilli, claystoneand sandstone, whereas in Prambanan are consist of sand, gravel, soil, rock fracture and sand clayed. Aquifer layer in Borobudur area are consist of sand, gravel , tuff and lapilli, whereas in Prambanan area are consist of sand and gravel. Base on its aquifer material, the groundwater potency in Prambanan area is higher than Borobudur area.Key words : rock stratigraphy, aquifer condition.